The Impact of Financial Ratios on the Dividend Payout Ratio in Coal Mining Companies - Aldo Sebastian; Rahmat Siauwijaya (Bina Nusantara University, 2021)
The purpose of this study is to determine the impacts of current ratio, debt to equity ratio, return on asset, total asset turnover ratio, and working capital turnover ratio on the dividend payout ratio in coal mining companies listed in Indonesia Stock Exchange 2016-2018. The sample used in this study was determined based on a purposive sampling method. The type of data used in this study is secondary data and the technique used to analyze the data in this study is panel data regression analysis. The results show that the debt to equity ratio has a negative and significant effect on the dividend payout ratio. While, current ratio, return on asset, total asset turnover ratio, and working capital turnover ratio have no significant effect on the dividend payout ratio.